Minimal residual disease in acute myeloid leukemia: current status and future perspectives - Kayser, Sabine (Current hematologic malignancy reports, 2015)
In acute myeloid leukemia (AML), the achievement of a morphological complete remission (CR) is an important milestone on the road to cure. Still, the majority of patients who achieve a morphological CR will eventually relapse. Thus, morphological means are not sensitive enough to detect clinically relevant tumor burdens left behind after therapy. Over the last years, several methodologies, particularly multiparameter flow cytometry and polymerase chain reaction, have emerged that can detect, quantify, and monitor submicroscopic amounts of leukemia cells (“minimal residual disease”, MRD). Newer techniques, such as next-generation sequencing, have not only changed our understanding of the molecular pathogenesis and clonal heterogeneity of AML but may also be used for MRD detection. Increasing evidence indicates that MRD could play an important role in dynamically refining disease risk and, perhaps, serve to fine-tune post-remission therapy in a risk-adapted manner, although the latter concept awaits validation through well-controlled trials. In this review, we discuss the current use of MRD measurements during AML treatment and highlight future perspectives.